Friction wheel transmission of no-tillage corn planters - Honglei, Jia; Zhang, Zhuo; Zhi, Chen; Tiezhi, Zheng; Jiale, Zhao; Mingzhuo, Guo (International Journal of Agricultural and Biological Engineering, 2017)
To overcome the unfavorable factors of ground wheel-driven chain transmission when a no-tillage planter operates on straw mulching fields, a friction wheel transmission based on ground wheel transmission was designed in this research. The stability, i.e., the effects of friction wheel tyre pressure on stability of machine transmission was investigated via validation of main factors. The relationships among tyre pressure, deformation and load were determined via theoretical analysis. The tyre pressure extreme for transmission is 25.90 psi, the maximum pressure imposed on the friction wheel tyre is 14 kN, the maximum deformation of friction wheel is 8.7 mm. The stabilities of friction wheel slip rate and seeding distance were investigated via field tests and alteration of friction wheel tyre pressure. After processing the test data, it can be found that the minimum tyre pressure for acquisition of friction wheel slip rate was 24.35 psi. After processing the data of seeding distance, it can be validated that the tyre pressure was kept unchanged following the optimal transmission effect of the transmission through the abrupt change of working speed, which further proved the feasibility of the new friction wheel transmission. The transmission of friction wheel can reduce 14.67% in variation coefficient of seed spacing at the speed of 5 km/h, and 16.22% at the speed of 8 km/h.Keywords: no-tillage planter, corn, friction wheel transmission, slip rate, field test, variation coefficient, seeding distanceDOI: 10.25165/j.ijabe.20171004.2565Citation: Jia H L, Zhang Z, Chen Z, Zheng T Z, Zhao J L, Guo M Z. Friction wheel transmission of no-tillage corn planters. Int J Agric & Biol Eng, 2017; 10(4): 87–97.